2021
DOI: 10.2478/jccm-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Hydroxyurea in the Treatment of COVID-19

Abstract: Introduction The rapid worldwide spread of COVID-19 motivated medical professionals to pursue and authenticate appropriate remedies and treatment protocols. This article aims to analyze the potential benefits of one treatment protocol developed by a group of care providers caring for severe COVID-19 patients. Methods The clinical findings of COVID-19 patients who were transferred to a specialized care hospital after unsuccess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…4 HU may also play a role in reducing the mortality of coronavirus disease 2019. 5 HU selectively acts on the most actively dividing cells such as basal layer keratinocytes. Hence, cutaneous adverse effects have been described, including xerosis, hyperpigmentation and skin atrophy and, less frequently, nonmelanoma skin cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 HU may also play a role in reducing the mortality of coronavirus disease 2019. 5 HU selectively acts on the most actively dividing cells such as basal layer keratinocytes. Hence, cutaneous adverse effects have been described, including xerosis, hyperpigmentation and skin atrophy and, less frequently, nonmelanoma skin cancers.…”
Section: Discussionmentioning
confidence: 99%
“…HU also has a role in selected skin conditions 4 . HU may also play a role in reducing the mortality of coronavirus disease 2019 5 . HU selectively acts on the most actively dividing cells such as basal layer keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study also revealed that the mortality rate was low in COVID-19 patients receiving hydroxyurea, suggesting a vital role of hydroxyurea in COVID-19 treatment [230]. Tamoxifen, a selective estrogen receptor modulator, had an interaction with CCNE1.…”
Section: Potential Drugs To Cure Severe Covid-19 Patientsmentioning
confidence: 99%